The Role of Financial Technology in the Analysis of Good Corporate Governance Efficiency Using the Data Envelopment Analysis Method - Nafidzi, Elman; Rachmadani, Fajar; Musthofa, Khabib; Futra, Ananda Aulia (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
The development of financial technology (fintech) has significantly influenced the banking industry, including Islamic banking, particularly in the implementation of Good Corporate Governance (GCG), which emphasizes transparency, accountability, and operational efficiency. This study aims to evaluate the efficiency of Good Corporate Governance (GCG) before and after the adoption of fintech in Islamic banks and to assess the extent to which fintech contributes to improving governance quality. The study employs Data Envelopment Analysis (DEA) as the primary analytical method, using input indicators such as operational costs, number of employees, and technology investment, and output indicators including risk management efficiency, reporting transparency, and compliance with sharia principles. The analysis focuses on several Islamic banks that have implemented fintech in their operational activities. The results indicate that fintech implementation significantly contributes to improving the efficiency of Good Corporate Governance (GCG). Banks that adopt fintech more rapidly achieve higher DEA scores, particularly in terms of transparency and risk management. Prior to fintech adoption, many Islamic Banks faced challenges related to high operational costs and inefficient governance practices. However, following fintech integration, there is a notable improvement in operational efficiency, as evidenced by comparative DEA scores across banks. In conclusion, the integration of fintech into Islamic Banking operations enhances the effectiveness of Good Corporate Governance (GCG), reduces risk exposure, and supports more transparent and accountable governance practices.